Predicting preventive strategies of acute myocardial infarction in young patients in Egypt: An observational analytical study in the form of cross-sectional study - Islam Elsayed Shehata; Basel Hatem; Mohamed Wafaei Aboul Enein; Ahmed Saeid Eldamanhory (Journal of Indian College of Cardiology, 2020)
Background: In the developing countries, coronary artery disease commonly occurred in younger people and is the main cause of mortality worldwide. Aim: This study aims to identify risk factors and characteristics of acute myocardial infarction (AMI) in young patients. To clarify the risk factors for AMI in young patients and the prevention for it, is very important problem worldwide. Patients and Methods: 650 ST-elevation myocardial infarction (STEMI) patients were included in our study. History taking, clinical examination, electrocardiography, echocardiography, and cardiac enzymes and coronary angiography were done to all patients; demographic data and risk factors including mental stress measured by the Standard Stress Scale, left ventricular (LV) dimensions, LV systolic and diastolic function, and angiographic characteristics were measured. We excluded patients with familial dyslipidemia and Type I diabetes. We classified the patients into two groups according to age: Group I – young – 142 patients <45 years and Group II – old – 508 patients >45 years. Statistical Analysis: Variables were expressed as the mean ± standard deviation. Percentage was used for categorical variables. t-test was used for comparison. Then, the significant univariate predictors were assessed by multivariate linear regression analysis to find the independent predictors for unfavorable outcome. Data analyses were performed with SPSS (version 21.0, Chicago Inc., Chicago, Illinois, USA). Results: Young patients were 142 (21.8%); males were majority between both groups. Smoking (56.3%), addiction (17.6%), mental stress (79.6%), and family history (4.2%) were significantly associated with young age group. Spontaneous coronary dissection (SCAD) (6.3%) and coronary spasm (10.5%) are relatively common cause of young AMI patients. SCAD and spasm has its specific risk factors such as young female and smoking, respectively. Anterior STEMI occurred in 59.1% of young patients and was the most common followed by Inferior STEMI in 31%. 14.8% of young patients presented late after 12 h of onset of symptoms. The multivariate logistic regression for independent predictors of unfavorable outcome showed that hypertension, Type II diabetes mellitus, Killip class, and multiple-vessel disease were significant predictors of unfavorable outcome. Conclusion: The prevalence of STEMI in young patients is increasing due to sedentary and stressful lifestyle and bad habits as smoking and addiction. Young patients have unique risk factor profile. STEMI in young occurred most often in males. Smoking is the most common risk factor. Anterior STEMI is the most common followed by inferior STEMI.